PROFESIONALISME GURU SEKOLAH DASAR: MEMBANGUN KOMUNITAS BELAJAR PROFESIONAL MELALUI BLENDED LEARNING - Puri Selfi Cholifah (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2017)
Professional development is one of the fundamental cores for teacher profession by involving collaboration through professional learning community. Some studies revealed a shifting paradigm from traditional to technology integrated professional learning community practice. Blended learning is an alternative solution in implementation of professional learning community that combines online and face-to-face learning. This paper explores conceptual analysis related to teacher professional development, professional learning community including collaboration, blended learning in this context, and professional learning community based on blended learning model.